Technology, organization and environment as a strategic factors of big data analytics readiness and acquisition in Malaysian libraries / Mohamad Salbihan Salman - Salman, Mohamad Salbihan (2023)
As we interact more online, the amount of data in Malaysian libraries always increases. With the large amount of data created, this phenomenon has created the phenomenon of big data (BD). Data analytics using BD can assist libraries in gaining actionable insights. Looking for a new research setting, big data analytics in Malaysian libraries is the central theme of this study. The discussion related to the theme has been well documented to understand the subject matter. The researcher also unveiled the TOE factor as a basis for the intention to adopt BDA. The study has identified several research gaps that led to this study. In current practice, BDA in Malaysian libraries is still new, and only a few libraries are using it. Most of the data has only been managed using descriptive analysis and is not well organised for decision-making. The limited amount of research pertaining to big data analytics (BDA) within the domain of libraries has resulted in a dearth of empirical studies examining the application of BDA in the field of library and information science. Hence, there is a lack of established theories, models, and frameworks to which one can refer. As a result, the Malaysian libraries lack reference sources to be used as guides. Besides that, the futility of previous studies in providing evidence on the relationship between TOE, BDAR, and the intention to adopt BDA Moreover, no framework consisting of the TOE, BDAR, and AITABDA has ever existed for library research. With that, four main objectives were derived, namely, to determine the TOE for BDAR in Malaysian libraries, to identify the level of BDAR in Malaysian libraries, to determine the effect of TOE on BDAR in Malaysian libraries, and to determine the effect of BDAR on the acquisition intention to adopt BDA.